Spectrophotometric determination of methyldopa in pharmaceutical formulations - Ribeiro, Paulo Roberto da Silva; Pezza, Leonardo; Pezza, Helena Redigolo (Eclética Química, 2005)
A new, simple, precise, rapid and low-cost spectrophotometric method for methyldopa determination in pharmaceutical preparations is described. This method is based on the complexation reaction of methyldopa with molybdate. Absorbance of the resulting yellow coloured product is measured at 410 nm. Beer’s Law is obeyed in a concentration range of 50 – 200 μg ml -1 methyldopa with an excellent correlation coefficient (r = 0.9999). No interference was observed from common excipients in formulations. The results show a simple, accurate, fast and readily applied method to the determination of methyldopa in pharmaceutical products. The analytical results obtained for these products by the proposed method are in agreement with those of the Brazilian Pharmacopoeia procedure at 95% confidence level.